2018
DOI: 10.23736/s0391-1977.18.02882-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of insulin-like growth factor system in the adrenocortical tumors

Abstract: The different presentation of adrenocortical tumors in benign adenoma (aca) or adrenocortical carcinoma (acc) is related to the variability at the molecular level. The insulin-like growth factor (igF) system is one of the most frequently altered pathways in acc. in this review we will critically analyze the evidence regarding the pathogenic role of the igF system in adrenal tumorigenesis, focusing on acc. We will also examine the preclinical and clinical studies which investigated the targeting of the igF syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 98 publications
(238 reference statements)
0
17
0
2
Order By: Relevance
“…IGF signaling is known to be activated in about 80-90% of cases (49,50) and the IGFR/IR inhibitor linsitinib has been demonstrated to be a promising targeted therapy for ACC by in vitro experiments (33). However, these encouraging findings have not been confirmed in clinical trials, although a small percentage of patients showed a partial response to treatment (24).…”
Section: Discussionmentioning
confidence: 99%
“…IGF signaling is known to be activated in about 80-90% of cases (49,50) and the IGFR/IR inhibitor linsitinib has been demonstrated to be a promising targeted therapy for ACC by in vitro experiments (33). However, these encouraging findings have not been confirmed in clinical trials, although a small percentage of patients showed a partial response to treatment (24).…”
Section: Discussionmentioning
confidence: 99%
“…ACC is associated with a poor prognosis, limited treatment options and high tumor recurrence rates (13). The pathogenetic mechanisms of ACC includes alterations of the Insulin-like Growth Factor system (35), Wnt/β-catenin pathway activation (36), TP53 mutations and prognostic molecular markers involved in cancer cell invasion properties and angiogenesis, appear to be very promising in elucidating of tumorigenesis and progression of ACC (37,38). However, the molecular mechanisms of ACC remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the mTOR and the IGF pathways in ACCs has been scantly investigated (10). As the mTOR pathway mediates some of the IGF effects (10, 35, 36), it could be involved in mediating the pathogenic effects of IGFs in ACCs. Therefore it might be important to understand whether a differential expression of the main components of the IGF pathway could influence the in vitro sensitivity to mTOR inhibitors and whether there is a rational to combine drugs targeting the IGF and the mTOR pathways.…”
Section: Relationship Between the Mtor And The Igf Pathways In Accsmentioning
confidence: 99%
“…Therefore, the expression of the main components of the mTOR and the IGF pathways seem not to be strongly related, which raises the questions whether in ACCs there is a dissociation between the expression of IGF2 and the activation of the classical IGF stimulated intracellular pathways, and whether the role of IGF2 in the pathogenesis of adult ACCs may have been overestimated, in agreement with some other recent speculations (38). However, it should also be considered that the complexity of the IGF system may have been underestimated since ACC expresses other components of the IGF pathway as well, such as the insulin receptor subtype A and the IGF2R (31, 36). These components have been scantly considered up today.…”
Section: Relationship Between the Mtor And The Igf Pathways In Accsmentioning
confidence: 99%